Aktivitas Inhibitor Alfa-Amilase Beberapa Tumbuhan Obat Indonesia - Akhmad Jaizzur Rijai; Asep Gana Suganda; Elin Yulinah Iskandar (Jurnal Sains dan Kesehatan, 2018)
Diabetes and its complication was major causes of death in most countries compared HIV/AIDS, tuberculosis and malaria. One approach in the treatment of diabetes is by slowing down the glucose absorption in the gastrointestinal tract, its can be achieved by inhibition of hydrolizing enzymes such as ?-amylase so the absorption of glucose becomes slow. This research aim was to determine the ?-amylase inhibitor activity from aqueous extract from some tradicional medicine plant such as daun insulin (Smallanthus sonchifolius (Poepp.) H.Rob), kembang bulan (Tithonia diversifolia (Hemsl.) Gray), bodhi leaf (Ficus religiosa L.), and Mahogany seeds (Swietenia mahagoni (L.) Jacq.). Extraction was done by reflux method using aquadest as a solvent. Extracts were obtained by freeze drying and tested for ?-amylase inhibitory activities. The IC50 value of daun insulin (EADI), kembang bulan leaf (EADKB), bodhi leaf (EADB) mahogany seeds (EABM) aqueous extract and acarbose as reference were 282,53; 473,85; 423,01; 220,91; and 3,42 ?g / mL, respectively. Keywords: alfa-amylase, traditional medicine plant, diabetes, IC50 and aqueous extract.